Association of salivary lactoferrin, Porphyromoras gingivalis and stress hormone levels in patients with periodontitis: a pilot study - Antequera, Desireé; Buetas, Elena; García-Esteban, Sandra; Romualdi, Deborah; Carrero, Laura; Municio, Cristina; Mira, Alex; Carro, Eva (Frontiers in Immunology, 2025)
BackgroundPeriodontitis is a prevalent inflammatory disease characterized by a dysbiotic oral microbiome, particularly involving Porphyromonas gingivalis (P. gingivalis) as a key periodontal pathogen. This disorder has also systemic implications, including links to neurodegenerative diseases such as Alzheimer’s disease (AD). Lactoferrin, an iron-binding glycoprotein involved in innate immunity, is found in elevated levels in inflammatory conditions, including periodontitis, and reduced in AD, likely due to hypothalamic-salivary gland axis dysfunction. Additionally, stress-related dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis may contribute to periodontal disease by altering immune responses, notably via elevated salivary cortisol and DHEA levels. The purpose of this study was to evaluate the relationship between salivary immune and stress biomarkers (lactoferrin, cortisol, DHEA) and the abundance of P. gingivalis with clinical periodontal parameters.MethodsA cohort of patients with and without a history of periodontitis was analyzed. Salivary and subgingival biofilm samples were collected to detect P. gingivalis levels using 16S rRNA gene sequencing and to quantify salivary biomarker concentrations by ELISA. Common clinical periodontal parameters, including periodontal pocket depth (PPD), clinical attachment level (CAL), bleeding on probing (BoP), and plaque index (PI) were recorded.ResultsPatients with a history of periodontitis showed significantly higher salivary lactoferrin, cortisol and DHEA levels compared to controls, along with increased P. gingivalis abundance. Strong correlations were observed between P. gingivalis levels and the salivary markers: lactoferrin, cortisol and DHEA. Moreover, lactoferrin, DHEA and cortisol also positively correlated with disease severity, based on the clinical periodontal parameters BoP PPD, CAL, and PI. Similarly, salivary and subgingival P. gingivalis positively correlated with BoP, but, specifically, subgingival P. gingivalis also correlated with PPD, CAL, and PI.DiscussionOur findings suggest that elevated lactoferrin, DHEA and cortisol levels reflect both immune-inflammatory and stress-mediated pathways in periodontitis, and its association with the abundance of P. gingivalis in saliva and subgingival area. This study supports immune and hormonal dysregulation in periodontal patients, with potential implications in systemic diseases, including such as AD, where lactoferrin levels are seriously altered.